2010
DOI: 10.1002/dc.21418
|View full text |Cite
|
Sign up to set email alerts
|

Multinational comparison of diagnostic clues for uterine cervical lesions among cytotechnologists in Asian countries

Abstract: Vaccination has been underway in several countries for sexually inactive young girls or women against HPV 16 and 18 to prevent them from infection of these HPV types and concurrent cancer development. However, uterine cervical cancers may remain uncontrolled among some Asian countries, where other types of HPV infection are more frequent. A sensitive cancer screening system would remain important for detection of the earlier stage cervical cancers in Asian countries. In this study, 130 cytotechnologists (CTs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Taniyama et al pointed out the same issue. They reported that the prevalence of HPV 52 infection may have been underestimated in previous studies and the HPV 52 type could be more prevalent than what has been reported in Asia, and as a result, the vaccination against HPV 16 and 18 would be less effective in Asia than that expected in the West [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taniyama et al pointed out the same issue. They reported that the prevalence of HPV 52 infection may have been underestimated in previous studies and the HPV 52 type could be more prevalent than what has been reported in Asia, and as a result, the vaccination against HPV 16 and 18 would be less effective in Asia than that expected in the West [ 16 ].…”
Section: Discussionmentioning
confidence: 99%